An Advanced Approach on the Study of Emulsion Polymerization: Effect of the Initial Dispersion State of the System on the Reaction Mechanism, Polymerization Rate, and Size Distribution of Polymer-Monomer Particles - Khaddazh, M.; Gritskova, I.A.; Litvinenko, G.I. (IntechOpen, 2012)
None